Stock Market Reaction to External CEO Appointments : Evidence from the Nordic Countries - Ahmed, Shaker; King, Timothy; Mäki, Juha (Palgrave Macmillan, 2025)
We study the short-horizon stock market reaction to firms appointing new CEOs from within the firm and outside its current ranks of executives. Given that external CEOs are likely to initiate more strategic changes due to their lack of commitment toward firms’ status quo, stock returns are expected to react differently to the hiring of external CEOs than the promotion of internal executives. Using a sample of large non-financial firms from four Nordic countries we find: (1) large Nordic firms depend more heavily on external CEOs and appoint more than half of appointees are outsiders, (2) only external CEO appointment announcements are associated with a positive abnormal stock return around event days, (3) firms’ operating performance does not increase in the following three years after the new CEO appointment, (4) however, firms with outside CEOs experience higher growth in sales and capital expenditure following their appointments.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|